An analysis of the non-English department students’ speaking ability at Universitas Riau - Rukmaryadi; M Zaim; Desvalini Anwar (English Instruction, 2020)
This descriptive research aimed to analyze and describe the speaking ability of non-English department students at Universitas Riau in the academic year 2016/2017. The study was also aimed to describe the activities done by the English lecturer in the teaching and learning process and the difficulties the students had in speaking. The data were gathered through observation, an oral test in the form of interview, and documentation. The participants of this study were 20 students majoring in Accounting, the Faculty of Economics. The findings of this research showed that the average score of students’ speaking was 2.36. This implies that the speaking ability of non-English Department students is categorized asFair.Then, this study also found that the English lecturer already applied the stages of teaching English through reading materials on certain topics, but lacked of oral activities in the first week of observation but with more speaking activities in the second week after a discussion was made between the class teacher and the researcher. In the case of the participants’ difficulties in speaking, it was noticeable that they had difficulties in pronunciation, grammar, vocabulary, and fluency. Thus, the lecturer should provide students the opportunity to have more practice in speaking in order to improve their ability in speaking.